Phase change, band gap energy and electrical resistivity of Mg doped TiO2 multilayer thin films for dye sensitized solar cells applications. Issue 17 (1st December 2019) - Khan, M.I.; Farooq, W.A.; Saleem, Muhammad; Bhatti, K.A.; Atif, M.; Hanif, Atif
Abstract: Magnesium doped Titanium dioxide (Mg: TiO2 ) thin films with 1, 3, 5 and 7 layers are deposited on FTO-glass substrates. XRD shows that the phases of TiO2 are changed by changing the number of coating layers. The 7th layered film has larger grain size than other layered films. The absorption is shifted towards the visible region when numbers of stacked layersare increased, according to the absorption spectra taken with UV–Vis spectrometer. The optical band gap energy (Eg ) of 1, 3, 5 and 7 layers films is 3.48, 3.34, 3.14 and 2.98 eV, respectively.The average sheet resistivity (Rs )measured by four point probe technique of 1, 3, 5 and 7 layered film is 5.68 x 10 5, 1.67 x 10 5, 3.99 x 10 4 and 6.34 x 10 2 ( Ω -cm), respectively. The efficiency of 7 layered based DSSC is 1.68% which is nearly 65% improved as compared with single layered based DSSC (i.e. 1.10%). This improvement in efficiency is due to increase in grain size and decrease in Eg .